2020
DOI: 10.1186/s13005-020-00237-z
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries in primary and permanent teeth in children’s worldwide, 1995 to 2019: a systematic review and meta-analysis

Abstract: Background Early childhood caries (ECC) is a type of dental caries in the teeth of infants and children that is represented as one of the most prevalent dental problems in this period. Various studies have reported different types of prevalence of dental caries in primary and permanent teeth in children worldwide. However, there has been no comprehensive study to summarize the results of these studies in general, so this study aimed to determine the prevalence of dental caries in primary and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
149
1
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(175 citation statements)
references
References 113 publications
5
149
1
20
Order By: Relevance
“…Dental caries is a common infectious disease that affects people of all ages and both genders worldwide. Although the prevalence of dental caries is decreasing, it can still be found in more than 50% of children [1,2]. The mechanism of dental caries fundamentally comes from the balance of demineralization and remineralization in the tooth structures [3].…”
Section: Introductionmentioning
confidence: 99%
“…Dental caries is a common infectious disease that affects people of all ages and both genders worldwide. Although the prevalence of dental caries is decreasing, it can still be found in more than 50% of children [1,2]. The mechanism of dental caries fundamentally comes from the balance of demineralization and remineralization in the tooth structures [3].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, dental caries in primary teeth continues to be an important oral health problem which affects a large part of the worldwide child population, with an overall prevalence of 46.2% [ 1 ]. The maintenance of deciduous teeth until exfoliation represents a crucial goal in pediatric dentistry to prevent aesthetic, phonetic and functional problems and to preserve the space for the eruption of permanent teeth [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review with a meta-analysis, which was recently published in order to determine the prevalence of this disease in primary and permanent dentition in children from different continents, showed that dental caries affects 46.2% and 53.8% of children in primary and permanent dentition, respectively [ 2 ]. Due to its worrying incidence and other characteristics that are related to its pathophysiological process, dental caries continues to represent an important public health problem in paediatric age [ 3 ].…”
Section: Introductionmentioning
confidence: 99%